Menanamkan Nilai Pancasila dalam Pendidikan Kewarganegaraan Pada Siswa Madrasah Ibtidaiyah/Sekolah Dasar - Ulya Sopa Aulia; Heri Hidayat; Heny Mulyani; Sofia Fauziah Azhar; Vivi Latifah (MADROSATUNA : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
ABSTRACT Education is something that must be obtained by every citizen of urban and remote rural villages. Currently, in welcoming the era of digitalization, Indonesia has to instill Pancasila values ​​in students from the start so that they understand Pancasila which is the basis of the unitary state of the Republic of Indonesia. The value of Pancasila is very appropriate when instilled in SD/MI children. This is so that after they grow up, they will get used to actions and behavior in accordance with the values ​​of Pancasila. Children really need guidance from others, especially parents, to instill these Pancasila values. This can be done through games, songs, recreation and other fun ways for children. However, SD/MI children also education also need to be given education at scholl, so that the cultivation of Pancasila values ​​is deeply embedded in their souls. Instilling morale in SD/MI children is also very necessary. Thus, children can develop attitudes and behaviors based on the values ​​of Pancasila, so that they grow into children who have noble morals who have morals according to the expectations of the nation, and to develop Pancasila values, habituation, awareness, practice and exemplary are needed. The purpose of this study is to provide a descriptive description of the related analysis the role of the moral values ​​of Pancasila in dealing with technological advances, in particular in the era of the Industrial Revolution 4.0. The research method used is descriptive analysis, where the results of the research are the need for a government role in returning national identity through Pancasila education and Moral Education since SD / MI so that the younger generation can work with Nusantara characters. Technology advances digital has a very big impact on the life of the nation. Disintegration moral is directly eroded by advances in technology and science.